DUALISME KELEMBAGAAN ANTARA PEMERINTAH KOTA DAN BADAN PENGUSAHAAN BATAM SERTA DAMPAKNYA TERHADAP KINERJA PEREKONOMIAN DI KOTA BATAM - Muhammad Zaenuddin; Wahyudi Kumorotomo; Samsubar Saleh; Agus H. Hadna (Politeknik Negeri Batam, 2017)
The development of special areas of Batam began in the 1970s. With the support of special regulations made by the central government, Batam City becomes a competitive place for investment in Indonesia. Moreover Batam has geographical advantage because of its strategic location and adjacent to Malaysia and Singapore. However, problems arise when the central government begins to impose regional autonomy. The birth of Batam City caused an overlapping of authority between the Local Government of Batam and the Batam Authority which caused the management of Batam Island to be not harmonious. This study aims to identify the problem of institutional dualism that occurred between the Local Government of Batam and the Batam Authority and its impact on economic performance in Batam City. This research is explanatory, the data used are primary and secondary data. The results show the fact that the main problems in governance in Batam City is the occurrence of dualism authority between the Local Government of Batam and the Batam Authority. This is shown by the fact that the overlapping of authority between Local Government of Batam and the Batam Authority occurs in several sectors, especially in land management, overlapping licensing in Batam, airport and port management. This condition led to a decline in economic performance in Batam and the decline of Batam's economic competitiveness.